Carbon network evolution from dimers to sheets in superconducting ytrrium dicarbide under pressure. Issue 1 (December 2018) - Feng, Xiaolei; Lu, Siyu; Pickard, Chris; Liu, Hanyu; Redfern, Simon; Ma, Yanming
Abstract Carbon-bearing compounds display intriguing structural diversity, due to variations in hybrid bonding of carbon. Here, first-principles calculations and unbiased structure searches on yttrium dicarbide at pressure reveal four new structures with varying carbon polymerisation, in addition to the experimentally observed high-temperature low-pressureI 4/mmm dimer phase. At low pressures, a metallicC 2/m phase (four-member single-chain carbide) is stable, which transforms into aPnma phase (single-chain carbide) upon increasing pressure, with further transformation to anImmm structure (double-chain carbide) at 54 GPa and then to aP 6/mmm phase (sheet carbide) at 267 GPa. Yttrium dicarbide is structurally diverse, with carbon bonded as dimers (at lowest pressure), four-member single chains, infinite single chains, double chains and eventually sheet structures on compression. Electron–phonon coupling calculations indicate that the high-pressure phases are superconducting. Our results aid the understanding and design of new superconductors and illuminate pressure-induced carbon polymerisation in carbides. Several rare earth carbides are superconducting at ambient pressure and low temperature. Here global structure searching predicts high-pressure metallic phases of yttrium dicarbide with phonon-mediated superconductivity and increased carbon network evolution from dimers to sheets with increasing pressure.